2005
DOI: 10.1007/s00425-005-1489-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of senescence-induced alteration in cytokinin metabolism on source-sink relationships and ontogenic and stress-induced transitions in tobacco

Abstract: Senescence and reserve mobilization are integral components of plant development, are basic strategies in stress mitigation, and regulated at least in part by cytokinin. In the present study the effect of altered cytokinin metabolism caused by senescence-specific autoregulated expression of the Agrobacterium tumefaciens IPT gene under control of the P(SAG12) promoter (P(SAG12)-IPT) on seed germination and the response to a water-deficit stress was studied in tobacco (Nicotiana tabacum L.). Cytokinin levels, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
51
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(62 citation statements)
references
References 50 publications
8
51
0
3
Order By: Relevance
“…15 Source-sink relations and reserve mobilization are key processes in both developmental and stress-induced ontogenic transitions and in the senescence process. 16 Generally speaking, allocation of resources is governed by changing metabolic gradients established by supply and demand that arise as a consequence of the dynamic between anabolic and catabolic respiratory processes. Of the carbohydrate-metabolizing enzymes, Ac INV contributes significantly to increased sugar availability for the establishment of metabolic sinks [17][18][19] it has been identified as an integral component of the molecular mechanism of cytokinin-mediated senescence delay 20 and activity is induced on exposure of tissue to LPE.…”
Section: A Role For Lpe In the Mitigation Of Senescence Progressionmentioning
confidence: 99%
“…15 Source-sink relations and reserve mobilization are key processes in both developmental and stress-induced ontogenic transitions and in the senescence process. 16 Generally speaking, allocation of resources is governed by changing metabolic gradients established by supply and demand that arise as a consequence of the dynamic between anabolic and catabolic respiratory processes. Of the carbohydrate-metabolizing enzymes, Ac INV contributes significantly to increased sugar availability for the establishment of metabolic sinks [17][18][19] it has been identified as an integral component of the molecular mechanism of cytokinin-mediated senescence delay 20 and activity is induced on exposure of tissue to LPE.…”
Section: A Role For Lpe In the Mitigation Of Senescence Progressionmentioning
confidence: 99%
“…This is an important result as it confirms that RAB17 promoter is active in sugarcane, is induced by stress (via stressinduced ABA), and facilitated the production of biologically active CKs in quantities required to elicit physiological and growth responses. This is also consistent with the strategy of conditional expression of IPT driven by other promoters like P SAG12 in tobacco (Cowan et al, 2005), wheat (Sykorova et al, 2008), creeping bentgrass (Xu et al, 2009) and cassava (Zhang et al, 2010) under drought stress. ABA levels observed in the plants here strongly correlated with the degree of stress.…”
Section: Discussionsupporting
confidence: 86%
“…This result is in line with the reports of IPT up-regulation in P SAG12 ::IPT transgenic tobacco (Cowan et al, 2005), wheat (Sykorova et al, 2008) creeping bentgrass (Xu et al, 2009) and cassava (Zhang et al, 2010) in response to drought stress treatment. In addition, we observed that IPT expression was also up-regulated under well-watered treatment in most of the P Ubi ::IPT plants which is expected as Ubi is a constitutive promoter (Christensen and Quail, 1996), however there was no obvious difference in the phenotype of these lines.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…The P SAG12 -IPT expression was activated at the onset of senescence in the basal leaves of tobacco plants and induced CK biosynthesis, which inhibited leaf senescence and, in turn, diminished P SAG12 -IPT activity. Nevertheless, P SAG12 -IPT transgenic plants displayed altered source-sink relations and nutrient deficiency in young leaves (7), delayed flowering (8), and reduced seedling establishment in response to water-deficit stress (9). We speculated that if the IPT gene could be expressed during plant maturation, but before the onset of senescence, CK production would not be limited to the old leaves, and thus, CK production would not alter nitrogen mobilization within the plant, and source/sink relationships would not be affected.…”
mentioning
confidence: 99%